De novo and inherited pathogenic variants in collagen‐related osteogenesis imperfecta. Issue 3 (24th January 2019) - Zhytnik, Lidiia; Maasalu, Katre; Duy, Binh Ho; Pashenko, Andrey; Khmyzov, Sergey; Reimann, Ene; Prans, Ele; Kõks, Sulev; Märtson, Aare
Abstract: Background: Osteogenesis imperfecta (OI) is a rare genetic bone fragility disorder. In the current study, differences between the genotypes and phenotypes of de novo and inherited collagen‐related OI were investigated. Methods: A comparative analysis was performed of the genotypes and phenotypes of 146 unrelated inherited and de novo collagen I OI cases from Estonia, Ukraine, and Vietnam. Mutational analysis of the subjects and all available parents were performed with Sanger sequencing. Results: Results showed that 56.16% of the OI cases were caused by de novo pathogenic variants. The proportion of OI types OI1, OI4, and OI3 among subjects with inherited OI was 45.31%, 46.88%, and 7.81%, respectively. Among subjects with de novo OI, the proportions of OI types (OI1, OI4, and OI3) were almost equal. Both inherited and de novo OI pathogenic variants occurred more often in the COL1A1 gene than in the COL1A2 . The majority of de novo cases were missense pathogenic variants, whereas inherited OI was mostly caused by loss of function pathogenic variants. Conclusion: In summary, there were significant differences between the phenotypes and genotypes of subjects with de novo and inherited OI. These findings may promote the further understanding of OI etiology, and assist with diagnostics procedures, as well as with family planning. Abstract : Majority of osteogenesis imperfecta cases have de novo nature. Out of studied 146 collagen‐related osteogenesis imperfecta patients from Estonia, Ukraine and Vietnam, 56% harbored de novo mutations. de novo and inherited osteogenesis imperfecta patients differed in phenotype severity and mutational spectrum.